2020
DOI: 10.1101/2020.11.02.365072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strong and localized recurrence controls dimensionality of neural activity across brain areas

Abstract: The dimensionality of a network's collective activity is the number of modes into which it is organized. This quantity is of great interest in neural coding: small dimensionality suggests a compressed neural code and possibly high robustness and generalizability, while high dimensionality suggests expansion of input features to enable flexible downstream computation. Here, for recurrent neural circuits operating in the ubiquitous balanced regime, we show how dimensionality arises mechanistically via perhaps t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 130 publications
(290 reference statements)
6
50
0
Order By: Relevance
“…5e-h, Extended Data Fig. 10) , and found that neural dynamics in S1 are strongly recurrent ( R 0.964 ± 0.008), similar to other cortical areas in rodents 36, 39, 44 . Importantly, we also observed that lower recurrence R prior to stimulation predicts higher detection probability (p 0.002, Fig.…”
Section: Strong Pre-stimulus Recurrent Interactions Prior To Miss Trialsmentioning
confidence: 68%
See 3 more Smart Citations
“…5e-h, Extended Data Fig. 10) , and found that neural dynamics in S1 are strongly recurrent ( R 0.964 ± 0.008), similar to other cortical areas in rodents 36, 39, 44 . Importantly, we also observed that lower recurrence R prior to stimulation predicts higher detection probability (p 0.002, Fig.…”
Section: Strong Pre-stimulus Recurrent Interactions Prior To Miss Trialsmentioning
confidence: 68%
“…Population variance is one measure of neural variability, which can arise from recurrent neural activity 36 . We quantified the recurrence R in order to test theories 65, 67, 68 about how it impacts signal propagation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We quantified the ratio of connected pairs with and without bidirectional connections and observed that reciprocal connections were 3 to 5 times more common than expected for a randomly connected network (red line) in E→E, E→I, I→E, and I→I connections (Fig 2A, bottom row). Further analysis of higher order connectivity motifs in our data and their impact on cortical computation is pursued in a parallel study (Dahmen et al, 2020).…”
Section: Distance Dependence Of Connectivitymentioning
confidence: 99%